2012
DOI: 10.1118/1.4738964
|View full text |Cite
|
Sign up to set email alerts
|

Validating plastic scintillation detectors for photon dosimetry in the radiologic energy range

Abstract: Purpose: Photon dosimetry in the kilovolt (kV) energy range represents a major challenge for diagnostic and interventional radiology and superficial therapy. Plastic scintillation detectors (PSDs) are potentially good candidates for this task. This study proposes a simple way to obtain accurate correction factors to compensate for the response of PSDs to photon energies between 80 and 150 kVp. The performance of PSDs is also investigated to determine their potential usefulness in the diagnostic energy range. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…Other authors declare an energy dependence of plastic scintillator detectors sensitivity in the radiologic energy range (25-150 kVp). 13,14,[16][17][18][19] As reported by Williamson et al, 16 Lessard et al, 18 and Peralta and Rêgo, 19 it is partly related to energy absorption differences between the reference dose medium and the scintillator medium (air and polystyrene respectively in our case). As shown in Figure 4, the polystyrene-toair mass energy-absorption coefficients ratio shows significant variations ,100 keV.…”
Section: Full Paper: Scintillating Fibre Detector For Small Animal Dosupporting
confidence: 56%
See 1 more Smart Citation
“…Other authors declare an energy dependence of plastic scintillator detectors sensitivity in the radiologic energy range (25-150 kVp). 13,14,[16][17][18][19] As reported by Williamson et al, 16 Lessard et al, 18 and Peralta and Rêgo, 19 it is partly related to energy absorption differences between the reference dose medium and the scintillator medium (air and polystyrene respectively in our case). As shown in Figure 4, the polystyrene-toair mass energy-absorption coefficients ratio shows significant variations ,100 keV.…”
Section: Full Paper: Scintillating Fibre Detector For Small Animal Dosupporting
confidence: 56%
“…[13][14][15] However, other studies also found an energy dependence of the dosemeter response, expressed as a decrease of sensitivity with decreasing energy. [16][17][18][19] In addition, in the kilovoltage energy range, the stem effect is mainly due to the fluorescence of the optical fibre and its contribution has been reported to be small. 8 Its small influence on the final signal allows to simplify the dosemeter readout system.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] In the current study, male nu/nu mice bearing HCT116 human colorectal tumor were treated by IT injection of tiopronin-coated GNPs (Tio-GNPs) and then irradiated with an X-ray source, which has a similar energy spectrum compared to that of the Papillon 50 X-ray unit (Figure 1). 24,25 The ligand that coats the GNP must be carefully chosen. Long ligands can attenuate the low-energy photoelectrons emitted from the GNPs after radiation, which could then lead to a considerable decrease in any radioenhancement effect.…”
mentioning
confidence: 99%
“…It is important that data used for treatment are determined in water or in a water-equivalent medium or that the irradiated medium is stated for data given in publications. 14,15 This article reports on the acceptance and commissioning work carried out on the T-200 X-ray therapy system manufactured by Wolf-Medizintechnik (WOmed) GmbH (WOmed, St Gangloff, Germany) installed at our clinic. The intended use of this machine is for superficial X-ray therapy using beams from tube potentials between 30 and 200 kV.…”
Section: Introductionmentioning
confidence: 99%